Decoupling of height growth and drought or pest resistance tradeoffs is revealed through multiple common-garden experiments of lodgepole pine. (13th January 2023) - Liu, Yang; Erbilgin, Nadir; Cappa, Eduardo Pablo; Chen, Charles; Ratcliffe, Blaise; Wei, Xiaojing; Klutsch, Jennifer G; Ullah, Aziz; Azcona, Jaime Sebastian; Thomas, Barb R; El-Kassaby, Yousry A
Abstract: The environment could alter growth and resistance tradeoffs in plants by affecting the ratio of resource allocation to various competing traits. Yet, how and why functional tradeoffs change over time and space is poorly understood particularly in long-lived conifer species. By establishing four common-garden test sites for five lodgepole pine populations in western Canada, combined with genomic sequencing, we revealed the decoupling pattern and genetic underpinnings of tradeoffs between height growth, drought resistance based on δ 13 C and dendrochronology, and metrics of pest resistance based on pest suitability ratings. Height and δ 13 C correlation displayed a gradient change in magnitude and/or direction along warm-to-cold test sites. All cold test sites across populations showed a positive height and δ 13 C relationship. However, we did not observe such a clinal correlation pattern between height or δ 13 C and pest suitability. Further, we found that the study populations exhibiting functional tradeoffs or synergies to various degrees in test sites were driven by non-adaptive evolutionary processes rather than adaptive evolution or plasticity. Finally, we found positive genetic relationships between height and drought or pest resistance metrics and probed five loci showing potential genetic tradeoffs between northernmost and the other populations. Our findings have implications for deciphering the ecological, evolutionary, and genetic bases of the decoupling of functional tradeoffs due to environmental change.